Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol for the syntheses of the protoberberine class of natural products - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Organic Letters, 2016)
A Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol has been developed for the synthesis of an 8-oxoprotoberberine core. It was successfully applied for the syntheses of (+/-)-8-oxocanadine, (+/-)-8-oxotetrahydropalmitine, and (+/-)-8-oxostylopine, which can be easily converted to the respective protoberberine natural products. The short synthetic route demonstrated would be useful for the synthesis of a large number of natural products and their analogues featuring a protoberberine scaffold.